Renal function recovery after laparosocopic pyeloplasty - Rivas, Juan Gómez (Polish Urological Association, 2014)
INTRODUCTION: To observe the renal function recovery measured by diuretic renography in short and medium follow–up of patients with transperitoneal Anderson–Hynes laparoscopic pyeloplasty. MATERIAL AND METHODS: We performed a retrospective review from our series of laparoscopic pyeloplasties, and we applied the following selection criteria: 1) to have at least two MAG3 diuretic renography during the follow–up, performed with a gap of 4–6 months between them; 2) to have at least one year follow–up. Fulfilling these criteria, we have selected 35 patents of 62. RESULTS: During follow–up, statistically significant improvement comparing with the pre–surgical value has been observed in diuretic renography in the operated kidney in all selected patients during the time of follow up in terms of: functional uptake ratio (FUR), furosemide excretion and total excretion. No statistically significant differences were found in excretion time and spontaneous excretion parameters. By dividing patients in two age groups <40 years and >40 years we found no statistically significant differences between them in relation to the improvement of the FUR. CONCLUSIONS: Laparoscopic pyeloplasty not only corrects the UPJO, it also may recover renal function demonstrated after one year follow up with diuretic renography. Laparoscopic pyeloplasty should be procedure of choice even in those patients with poor renal function at diagnosis, whenever there are chances of recovering renal function, regardless patients age.